The challenges of being an in-house AI ethicist and how to overcome them - Dafna Burema (Journal of Responsible Innovation, 2025)
The ‘institutional turn’ to AI ethics signifies the establishment of the profession of an in-house AI ethicist. Reflecting on my own experience working as an in-house AI ethicist at an academic institution, this essay discusses three challenges of the profession: ambiguous objectives, conflict of interest, and epistemological differences. With these three challenges, the job requires performing several roles in parallel (i.e. auditor, educator, researcher, collaborator), coping with different stakeholders, and overcoming disciplinary approaches to AI ethics. Ultimately, the in-house AI ethicist participates in a balancing act, in which they have to constantly question their own positionality in relation to the institutional context. To overcome these challenges, practitioners could approach the job as ethnographic fieldwork.